2003
DOI: 10.3987/com-03-9739
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Substituted Dibenz-oxazepines and Dibenzthiazepine Using of 4-Bromo-5-nitrophthalonitrile

Abstract: Proposed a method of synthesis of new cyano containing compounds of oxazepine and thiazepine series based on activated aromatic nucleophilic substitution reaction of bromine atom and nitro group in 4-bromo-5nitrophthalonitrile by various bifunctional O-, N-, S-nucleophiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Despite the progress made recently in this field, alternative methods of synthesizing these compounds continue to be developed. First of all, it should be noted that S N Ar-reactions occurring with the participation of 4-nitro-and 4-bromo-5-nitrophthalonitrile under homo-and hetero-conditions allow the study of the synthesis of a large number of diverse aromatic and heterocyclic compounds, [17][18][19][20][21][22][23] and related compounds that are condensed with the phthalonitrile fragment (Scheme1). In addition, we have developed methods for the synthesis of 3-substituted 2-amino-1-hydroxy-1H-indole-5,6-dicarbonitriles (2), [24] and 2-aryl-1-Hydroxy-1H-indole-5,6-dicarbonitriles (3), [25] based on 4-bromo-5-nitrophthalonitrile (1) (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the progress made recently in this field, alternative methods of synthesizing these compounds continue to be developed. First of all, it should be noted that S N Ar-reactions occurring with the participation of 4-nitro-and 4-bromo-5-nitrophthalonitrile under homo-and hetero-conditions allow the study of the synthesis of a large number of diverse aromatic and heterocyclic compounds, [17][18][19][20][21][22][23] and related compounds that are condensed with the phthalonitrile fragment (Scheme1). In addition, we have developed methods for the synthesis of 3-substituted 2-amino-1-hydroxy-1H-indole-5,6-dicarbonitriles (2), [24] and 2-aryl-1-Hydroxy-1H-indole-5,6-dicarbonitriles (3), [25] based on 4-bromo-5-nitrophthalonitrile (1) (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…While some degree of delocalization of the negative charge in 4 is probably needed to enable formation of the latter, replacing the carbonyl substituent in 1f with a (hetero)aromatic substituent ( 9 ) may serve the purpose and favor the Smiles rearrangement for those substrates 2 which previously did not yield [1.4]oxazepines 8 (Figure ). Herein, we present the outcome of testing this hypothesis …”
Section: Introductionmentioning
confidence: 99%
“…In this work aimed at the utilization of aromatic polynitro compounds, we found that cyclization of ortho-nitrobenzoic acid 2-hydroxyanilides afforded dibenz[b,f] [1,4]oxazepin-11(10H)-ones. 6,7 We demonstrated that intramolecular nucleophilic displacement of a nitro group in 2,4,6-trinitrobenzoic acid amides A is a general method of preparing benzoannulated seven-and eightmembered N-containing heterocycles B (Scheme 1).…”
mentioning
confidence: 99%